First Report of Nipaecoccus viridis (Hemiptera: Pseudococcidae) Associated with Citrus Production in the United States. (22nd May 2020) - Diepenbrock, Lauren M; Ahmed, Muhammad Z
Abstract: Nipeacoccus viridis (Newstead), is an invasive, polyphagous mealybug pest recently found causing damage in citrus production fields in several counties in Florida, United States. In this short communication, we document the finding of this pest, its associated damage in citrus groves, and provide basic diagnostic and scouting information. Nipaecoccus viridis is a pest of concern, necessitating the quick development of management tools.